Heterogeneidad textual y neovanguardia: los poemas acéntricos y quipullagemas de José Luis Ayala - Iubini Vidal, Giovanna (2018)
It analyses the textual proposals in the work of the poet Puno José Luis Ayala, especially the poems Acéntricos and Quipullagemas of Kabbalah for Immigrants (Antilaveno/Poemallages). It proposes that these textual experiments constitute a form of textual heterogeneity, a frontier writing that defies epistemological, cultural and literary systems, whose purpose is the extension of the notion of literature. Its special neovanguardista condition becomes the link between the aesthetics of the Andean avant-garde, mainly of Oquendo de Amat and Andean cultural matrices like the quipu.